Kepatuhan Syariah dan Keadilan dalam Pembiayaan Kendaraan Berbasis Akad Murabahah pada Lembaga Pembiayaan Non-Bank - Didi Suardi; Ajie Pangestu; Aisyah Defy R. Simatupang; Martavevi Azwar (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2026)
This study analyzes the implementation of the Murabahah contract at BFI Finance Syariah Bogor, a non-bank Islamic finance institution, focusing on Sharia compliance and transactional fairness. Using a qualitative-descriptive and normative-legal approach, data were collected through interviews, observations, and document analysis. Findings indicate that the institution complies with the principle of al-milk qabla al-bai‘ and avoids riba by engaging in genuine sales transactions. However, limitations were identified in profit-margin transparency, centralized Sharia Supervisory Board (DPS) oversight, and customers’ limited understanding of Sharia principles. The policy of interest-free delay penalties reflects the values of ta‘āwun (cooperation) and iḥsān (benevolence), aligning with maqāṣid al-sharī‘ah objectives in protecting wealth and ensuring social justice. The study highlights the need for transformation from formal to value-based Sharia compliance through pre-contract education, decentralized supervision, and stronger ethical governance in Islamic finance.